Strategic value of electronic human resource management: case financial institution - Mäkinen, Joni (My University, 2013)
It has become obligatory for HR function to meet the current challenge of displaying the means to generate organisational value. Consequently, HR departments have been forced in a changing environment to be strategic, flexible, and adjusted to customer requirements. When adding to this setting the fact that the demand for capable talents has become even greater, technological innovations such as e-HRM are seen by many standards as a key for success. Furthermore, increasing internal demands have fostered the implementation rate of e-HRM to design and deliver HR efficiently. Therefore, the use of technology is seen a viable way for HR to create strategic value. The purpose of this paper was to analyse the strategic role of electronic human resource management in creating value. To deliver answer to this purpose three research questions were formed. The first RQ1 was aimed to deliver understanding of the organisational culture, in which e-HRM is set to operate, what HR functions are done internally and why, and finally how the e-HRM has influenced in the delivery of HR services. The second RQ2 investigates the means of which e-HRM is expected to serve for HRM to become more strategic. The thirds RQ3 was aimed to convey insight about the perceptions of strategic value of e-HRM and how this value is seen among different levels of managers, units, and corporate HQ. This research is a qualitative research and a single case study approach was used to understand the phenomenon at the case company. Data for this research was collected through face-to-face semi-structured interviews. Main findings of the research show that e-HRM has been able to provide strategic value at the case company by facilitating management capabilities, bringing efficiency to HR processes, and providing means to enhance HR partners role as strategic partners. However, it was also discovered that the gained efficiencies are hindered by poor user-friendliness, process design, and user-engagement capabilities. The findings provide evidence that e-HRM can provide strategic value, which may lead to competitive advantage, if a careful due diligence of its match to organisation characteristics is made and system’s intended role is understood and clarified to employees.
Keywords: e-HRM; Information Systems; Human Resource Management; HR roles; Talent Management; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|